2008
DOI: 10.1093/aob/mcn064
|View full text |Cite
|
Sign up to set email alerts
|

Physical Dormancy in Seeds of the Holoparasitic Angiosperm Cuscuta australis (Convolvulaceae, Cuscuteae): Dormancy-breaking Requirements, Anatomy of the Water Gap and Sensitivity Cycling

Abstract: Whereas bulges adjacent to the micropyle act as the water gap in other species of Convolvulaceae with physical dormancy, the hilar fissure serves this function in Cuscuta. Cuscuta australis can cycle between insensitivity <--> sensitivity to dormancy-breaking treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 42 publications
3
55
0
1
Order By: Relevance
“…initial route of water into the seed after PY is broken) in seeds of S. angulatus (X. Qu, unpubl. 2008), as it is in Cuscuta australis (Jayasuriya et al . 2008), was the only place for entrance of water into the seed (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…initial route of water into the seed after PY is broken) in seeds of S. angulatus (X. Qu, unpubl. 2008), as it is in Cuscuta australis (Jayasuriya et al . 2008), was the only place for entrance of water into the seed (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…Conceptual models of sensitivity cycling find dormancy break are shown in figures 11 and 12. Heretofore, seeds of species that belong to distantly related tribes of Convolvulaceae (sensu Stefanovic et al 2003) were reported to cycle between insensitivity and sensitivity to dormancy-breaking treatment {Ipomoea laciinosa |Ipomoeeae; Jayasuriya et al 2ÜÜ8IÍ|, Cuscuta australis |Ciiscuteae; Jayasuriya et al 2008c], and jacquemontia ovalifolia ¡Jacquemonteae; Jayasuriya et al 2008 b\]. Ipomoea bederacea and /.…”
Section: Discussionmentioning
confidence: 99%
“…No germination of those seeds was recorded at low temperatures (5ºC, 10ºC and 15ºC) or high temperatures (40ºC and 45ºC) and the percentage of germination was highest at 30ºC (20.63%). On the other hand, dry storage for two months had been found in another study to result in 65% germinated seeds of Cuscuta australis, while weak germination (8-9%) was found after moist storage (Jayasuriya et al, 2008). The authors found that C. australis seeds dipped in boiling water for a period of 10 s increased germination to 75%, while the percentage of germinated seeds decreased with increasing duration of dipping (15 s and 20 s).…”
Section: Results and Disscusionmentioning
confidence: 91%